1923
DOI: 10.3181/00379727-20-216
|View full text |Cite
|
Sign up to set email alerts
|

The specific soluble substance of pneumococcus

Abstract: hydrolysis of the collagen, although the organized skin structure inhibited diffusion of the enzyme and greatly decreased the speed of the reaction.Specimens of collagen tanned with quinone, gallotannic acid, copper sulfate and formaldehyde were all hydrolyzed by trypsin while chrome tanned collagen was not.In 1917 Dochez and Averyl showed that there was contained in filtrates from pneumococcus cultures and in the body fluids of experimentally infected animals and of patients suffering from pneumonia, a solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
4

Year Published

1927
1927
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 5 publications
(5 reference statements)
0
35
0
4
Order By: Relevance
“…Beginning in the early 1900s, a number of attempts were made to use killed pneumococci as vaccines; these efforts generally suffered from lack of knowledge of antigenic structure and variation, but some efficacy against pneumonia was shown (9, 10). In the 1920-1940s, scientists at Rockefeller Institute showed that pneumococcus expresses a variety of capsular polysaccharides (CPs), that these CPs are its major virulence factor, that these CPs are antigenic (the first non-protein thus shown), that these CPs are the basis of serological type, and notably, that transformation of one type to another is specified by DNA, opening inquiry into the biochemical basis of inheritance (11,12). The CPs impede clearance of the bacteria by phagocytic cells, and anti-CP antibodies confer serotype-specific protection by coating the capsulated bacteria to facilitate adherence by phagocytes (opsonization).…”
Section: History Of Vaccinationmentioning
confidence: 99%
“…Beginning in the early 1900s, a number of attempts were made to use killed pneumococci as vaccines; these efforts generally suffered from lack of knowledge of antigenic structure and variation, but some efficacy against pneumonia was shown (9, 10). In the 1920-1940s, scientists at Rockefeller Institute showed that pneumococcus expresses a variety of capsular polysaccharides (CPs), that these CPs are its major virulence factor, that these CPs are antigenic (the first non-protein thus shown), that these CPs are the basis of serological type, and notably, that transformation of one type to another is specified by DNA, opening inquiry into the biochemical basis of inheritance (11,12). The CPs impede clearance of the bacteria by phagocytic cells, and anti-CP antibodies confer serotype-specific protection by coating the capsulated bacteria to facilitate adherence by phagocytes (opsonization).…”
Section: History Of Vaccinationmentioning
confidence: 99%
“…In this connection, there comes to mind the work of Avery and Heidelberger (8)(9)(10), .who, basing their conclusions upon precipitin tests, attribute the type specificity of the pneumococcns to a substance of carbohydrate nature while a nucleoprotein is designated as the carrier of the species specificity of the organism. On the other hand, Zinsser and his associates (11)(12)(13)(14) have prepared, from various bacteria, including also the pneumococcus, substances--residue antigens--which are free from coagulable protein and are capable of reacting specifically in a precipitin test with the homologous antiserum.…”
Section: Alcoholic Extracts Of P N E U M O C O C C Imentioning
confidence: 99%
“…that Avery persuaded Michael Heidelberger to join his department. Their work led to the isolation and characterization of the specific capsular polysaccharides of the first three types of pneumococci (Heidelberger & Avery, 1923, 1924Heidelberger, Goebel & Avery, 1925). The purified preparations, first made, were non-antigenic when inoculated into rabbits, and were regarded as haptenes.…”
mentioning
confidence: 99%
“…Following the lead given by the work of Avery, specific serological reactivity was later shown to be due to polysaccharides in other bacterial groups -the tubercle bacillus, Friedlander's bacillus, Haemophilus influenzae, Salmonella and other organisms. Avery's group showed that there was serological cross-reactivity between polysaccharides from type I1 pneumoccoci, from a strain of Friedlander's bacillus (Avery, Heidelberger & Goebel, 1925) and from gum arabic (Heidelberger, Avery & Goebel, 1929). These cross-reactions were in part explained by the studies of Avery and Goebel, published in eight papers between 1929 and 1934, on conjugated carbohydrate-proteins.…”
mentioning
confidence: 99%